2012
DOI: 10.4103/0972-2327.99708
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of thyrotoxic periodic paralysis from idiopathic hypokalemic periodic paralysis: An experience from India

Abstract: Objective:There is paucity of reports on thyrotoxic periodic paralysis (TPP) from India. We report the patients with TPP and compare them with idiopathic hypokalemic periodic paralysis (IHPP).Materials and Methods:Patients with hypokalemic periodic paralysis (HPP) treated during the past 11 years were evaluated retrospectively. Their demographic parameters, family history, clinical features, precipitating factors, severity of weakness, laboratory parameters and rapidity of recovery were recorded. The demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Although TPP is commonly seen in patients with GD with overt hyperthyroidism, thyrotoxic symptoms may be absent at the time of TPP attack in 10 to 25% of the patients (2-6). Kalita et al (12) showed that two thirds of the patients with TPP had subclinical hyperthyroidism at the time of presentation. Hegde et al (2) described a 32-year-old Asian male who presented with acute-onset weakness and hypokalemia with no previous history of thyroid disorder or any signs and symptoms suggestive of hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Although TPP is commonly seen in patients with GD with overt hyperthyroidism, thyrotoxic symptoms may be absent at the time of TPP attack in 10 to 25% of the patients (2-6). Kalita et al (12) showed that two thirds of the patients with TPP had subclinical hyperthyroidism at the time of presentation. Hegde et al (2) described a 32-year-old Asian male who presented with acute-onset weakness and hypokalemia with no previous history of thyroid disorder or any signs and symptoms suggestive of hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…THPP is a rare manifestation of hyperthyroidism characterised by episodic proximal muscle weakness which increases and decreases 1. It most frequently affects Asian males with hyperthyroidism in the second and third decades of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…1 Only few cases are reported in the literature that showed respiratory paralysis due to hypokalemia in distal RTA. Distal RTA is of two types: inherited or acquired.…”
Section: Discussionmentioning
confidence: 99%